P488 Trends in corticosteroid (CS) use over time and following diagnosis in patients with Inflammatory Bowel Disease (IBD), using IBM® MarketScan®. (21st January 2022) - Raine, T; Melmed, G Y; Finney-Hayward, T; Clark, R; Chapman, J C; Targownik, L; Burisch, J; Olen, O
Abstract: Background: As part of the IBD-DICE (Determinants, Incidence and Consequences of CS Excess) collaborative research programme, this study examined rates of CS use and excess use in patients with IBD over time and after initial diagnosis. Methods: Using IBM ® MarketScan ®, a representative claims database including details of >200 million individuals annually in the United States (US), we conducted a retrospective analysis of CS use from 2007 to 2018 in adult patients with IBD. Patients with conditions commonly associated with high levels of CS use (other than IBD) were excluded. CS use and excess were examined over calendar time in all patients (prevalent cohort), and in relation to the time of first IBD diagnosis in a newly diagnosed subset (incident cohort). Both a restrictive and a broader definition of CS use were examined. The restrictive definition only included claims for oral budesonide or prednisolone/prednisone with a pre-defined minimum daily equivalent dose of ≥17.5 mg, based on a typical tapering CS prescription for IBD. Under the broader definition, CS use was considered as any claim for oral prednisolone, prednisone, budesonide or methylprednisolone. Excess CS use was defined as either ≥2 CS courses in a 12-month period or ≥3 months of continuous CS use. Results: The prevalent cohort (restrictive definition) included a total of 338, 837 patients with 1, 051, 213 observation years. Rates of CS use ranged from 23.7% in 2007 to 19.3% in 2009 and plateaued in subsequent years (18.4%–21.1%). Rates of CS excess were higher from 2007 to 2009 (8.9%–11.5%) than in later years, and remained relatively stable from 2010 to 2018 (7.9%–8.6%). Similar patterns were seen with the broad definition of CS use, with CS excess rates of 15.2% in 2007 and 10.9%–11.8% from 2010 to 2018 (Figure 1). The incident cohort included 106, 875 patients with 320, 295 observation years. CS use was highest in the first year after diagnosis (24.2% and 29.4% with the restrictive and broad definitions, respectively) and decreased and plateaued by the second year after diagnosis (range: 10.8%–14.8% and 16.8%–21.0%, respectively). Similarly, CS excess was highest in the first year after diagnosis (11.7% and 14.6% with the restrictive and broad definitions, respectively) and decreased and levelled off by the second year after diagnosis (range: 3.6%–6.2% and 5.6%–8.6%, respectively) (Figure 2). Conclusion: Despite advances in IBD treatment over the past decade and the adverse effects associated with CS, use of CS has not decreased substantially in the US in recent years. Levels of CS excess remain a concern, and may represent an opportunity for more optimised treatment and education, especially for newly diagnosed patients.